Investigating lattice strain impact on the alloyed surface of small Au@PdPt core–shell nanoparticles. Issue 16 (8th April 2020) - Williams, Benjamin P.; Yaguchi, Momo; Lo, Wei-Shang; Kao, Chen-Rui; Lamontagne, Leo K.; Sneed, Brian T.; Brodsky, Casey N.; Chou, Lien-Yang; Kuo, Chun-Hong; Tsung, Chia-Kuang
Abstract : We investigated lattice strain on alloyed surfaces using ∼10 nm core–shell nanoparticles with controlled size, shape, and composition. Abstract : We investigated lattice strain on alloyed surfaces using ∼10 nm core–shell nanoparticles with controlled size, shape, and composition. We developed a wet-chemistry method for synthesizing small octahedral PdPt alloy nanoparticles and Au@PdPt core–shell nanoparticles with Pd–Pt alloy shells and Au cores. Upon introduction of the Au core, the size and shape of the overall nanostructure and the composition of the alloyed PdPt were maintained, enabling the use of the electrooxidation of formic acid as a probe to compare the surface structures with different lattice strain. We have found that the structure of the alloyed surface is indeed impacted by the lattice strain generated by the Au core. To further reveal the impact of lattice strain, we fine-tuned the shell thickness. Then, we used synchrotron-based X-ray diffraction to investigate the degree of lattice strain and compared the observations with the results of the formic acid electrooxidation, suggesting that there is an optimal intermediate shell thickness for high catalytic activity.